Scimitar Syndrome and H-type Tracheo-esophageal Fistula in a Newborn Infant - Allison Lastinger; Malek El Yaman; Robert Gustafson; Panitan Yossuck (Pediatrics and Neonatology)
Scimitar syndrome is a rare congenital anomaly characterized by partial anomalous pulmonary venous drainage of the right lung to the inferior vena cava (IVC) creating a tubular opacity paralleling the right cardiac border on chest radiography which resembles a curved Turkish sword or scimitar. Associated pulmonary and vascular anomalies have been reported in cases of Scimitar syndrome, most commonly hypoplasia of right lung, dextroposition of the heart, hypoplasia of the right pulmonary artery, and aberrant arterial supply from the descending aorta to the affected lobe of the right lung. To the best of our knowledge, this is the first case of Scimitar syndrome with an H-type tracheoesophageal fistula that has ever been reported.